The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1021/ic00144a024
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and magnetic properties of Cu2Cl2(C5H5N)2(OCH3)2: a catalytic species related to the copper(II)-induced oxidation of phenols

Abstract: PPh2)2Rh(COD) should be half the number in [Rh(/t-PPh2)(COD)]2, if both COD ligands are lost from the latter. The rate of hydrogenation of 1-octene with [(DPPE)Rh(/u-PPh2)2Rh(COD)] is actually greater than the rate for [Rhgrants that aided the purchase of the 300-and 200-MHz NMR instruments, respectively. We also thank Professor G. G. Christoph for help with the X-ray structure determination and the John Simon Guggenheim Foundation for a fellowship to D.W.M. for 1981-1982.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…It has been reported that in the methoxyl-bridged Cu 2 O 2 unit there is an antiferromagnetic interaction when the Cu-O-Cu angle is larger than 95.71 and a ferromagnetic interaction when the Cu-O-Cu angle is smaller than 95.71. 19,23,24 In complex 6, the methoxyl-bridged Cu1-O51-Cu2 and Cu1-O52-Cu2 angles are 98.5(2) and 98.3(2)1, respectively, suggesting the presence of an antiferromagnetic intra-dimer interaction. The plot of w M À1 vs. T is shown in Fig.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…It has been reported that in the methoxyl-bridged Cu 2 O 2 unit there is an antiferromagnetic interaction when the Cu-O-Cu angle is larger than 95.71 and a ferromagnetic interaction when the Cu-O-Cu angle is smaller than 95.71. 19,23,24 In complex 6, the methoxyl-bridged Cu1-O51-Cu2 and Cu1-O52-Cu2 angles are 98.5(2) and 98.3(2)1, respectively, suggesting the presence of an antiferromagnetic intra-dimer interaction. The plot of w M À1 vs. T is shown in Fig.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…A commonly used group of molecules for these purposes are nitrogen donor ligands. Aromatic pyridines and polypyridines [14][15][16][17] are typical examples of such molecules. Non-aromatic rings such as piperidine and piperazine have also been used for construction of extended copper halide structures.…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxoand alkoxo-bridged Cu(II) complexes exhibit magnetic behaviour ranging from the antiferromagnetic to ferromagnetic depending on the geometry of Cu 2 (OR) n (n = 1 and 2, R = H, alkyl, aryl) binding units. [16][17][18][19][20][21][22][23][24][25][26][27][28] The well-studied hydration reaction of the di-pyridylketone (dpk) ligand has been implemented to construct several metal clusters, in which the two pyridyl N atoms and the gem-diol obtained from metal-promoted hydration act as four potential donor sites and the resulting M(II)-dpk-azide (M = Co, Ni) compounds have been characterized so far to be isomorphous. 14c, 29 Herein, an analogous hydration reaction would be expected using di-pyridylketone azine (dpka) (Scheme 1) for the assembly of metal clusters and the hydration or solvolysis reaction will occur at the imino group to widen the range of structural arrangements.…”
Section: Introductionmentioning
confidence: 99%